Advancing tritium self-sufficiency in fusion power plants: insights from the BABY experiment - Rémi Delaporte-Mathurin; Nikola Goles; John Ball; Collin Dunn; Emily Edwards; Sara Ferry; Edward Lamere; Andrew Lanzrath; Rick Leccacorvi; Samuele Meschini; Ethan Peterson; Stefano Segantin; et al. (Nuclear Fusion)
In the pursuit of fusion power, achieving tritium self-sufficiency stands as a pivotal challenge. Tritium breeding within molten salts is a critical aspect of next-generation fusion reactors, yet experimental measurements of Tritium Breeding Ratio (TBR) have remained elusive. Here we present the results of the Build A Better Yield blanket experiment, which represents a pioneering effort in tritium research by utilizing high-energy (14 MeV) neutron irradiation of molten salts, a departure from conventional low-energy neutron approaches. Using a small-scale (100 ml) molten salt tritium breeding setup, we not only simulated, but also directly measured a TBR ( $3.57× 10^{-4}$ ). This innovative approach provides crucial experimental validation, offering insights unattainable through simulation alone. Moreover, our findings reveal a surprising outcome: tritium was predominantly collected as HT, contrary to the expected TF. This underscores the complexity of tritium behavior in molten salts, highlighting the need for further investigation. This work lays the foundation for a more sophisticated experimental setup, including increasing the volume of the breeder, enhancing neutron detection, and refining tritium collection systems. Such improvements are crucial for advancing our understanding of fusion reactor feasibility and paving the way for future experiments.